Effect of the Capability-Opportunity-Motivation Behavior (COM-B) model of dietary behavior program on gestational weight gain in Thailand: A randomized controlled trial - Buakhai, Pantipa; Xuto, Piyanut; Klunklin, Pimpaporn; Thungjaroenkul, Petsunee (Belitung Raya Publisher - Belitung Raya Foundation, 2026)
Background: Excessive gestational weight gain can adversely affect maternal and fetal health. Dietary behavior change can help control gestational weight gain and prevent adverse pregnancy outcomes. Objective: This study aimed to examine the effect of the Capability-Opportunity-Motivation Behavior (COM-B) model of dietary behavior program on gestational weight gain. Methods: This single-blind randomized controlled trial used a pre-posttest control group design and included 96 pregnant women from a northern province of Thailand. Participants were randomly assigned equally to the experimental and control groups (48 each) using permuted block randomization. The experimental group received a 14-session COM-B model of dietary behavior program, while the control group received usual care. Data were collected via questionnaires between November 2023 and October 2024, and were analyzed using SPSS version 26, employing descriptive and inferential statistical methods. Results: At 36 weeks’ gestation, pregnant women in the experimental group had a significantly lower mean difference in gestational weight gain based on the Institute of Medicine (IOM) recommendation compared with both their baseline at 20 weeks and the control group. After adjusting for maternal age and education, the experimental group continued to show significantly lower gestational weight gain than the control group. The adjusted intention-to-treat analysis indicated a mean difference of -2.227 kg (95% CI: -3.75 to -0.70; p = 0.005; partial η² = 0.084), while the adjusted per-protocol analysis showed a mean difference of -2.648 kg (95% CI: -4.31 to -0.99; p = 0.002; partial η² = 0.110). These results suggest that the COM-B model of dietary behavior program effectively limited gestational weight gain, independent of sociodemographic differences. Even modest reductions in gestational weight gain may contribute to lowering the risk of pregnancy complications such as gestational diabetes and preeclampsia. Dietary behavior change was monitored, but not a predefined secondary outcome. Conclusion: The COM-B model of dietary behavior program led to minimal but potentially clinically relevant reductions in gestational weight gain. The findings highlight the clinical relevance of nurse-led interventions, underscoring the need for nurse training to implement the program in routine antenatal care. Trial Registry Number: Thai Clinical Trials Registry (TCTR20230907001)